Lenin's Terror : the Ideological Origins of Early Soviet State Violence - Ryan, James (Routledge contemporary Russia and Eastern Europe series., 2012)
This book explores the development of Lenin's thinking on violence throughout his career, from the last years of the Tsarist regime in Russia through to the 1920s and the New Economic Policy, and provides an important assessment of the significance of ideological factors for understanding Soviet state violence as directed by the Bolshevik leadership during its first years in power. It highlights the impact of the First World War, in particular its place in Bolshevik discourse as a source of legitimating Soviet state violence after 1917, and explains the evolution of Bolshevik dictatorship.